Celestia - Fior, Manuele (Fantagraphics Books, 2021)
"Celestia has become an outpost for criminals and other misfits, as well as a refuge for a group of young telepaths. Events push two of them, Dora and Pierrot, to flee the island and set sail to the mainland. There, they discover a world on the precipice of a metamorphosis, though also a world where adults are literally prisoners of their own fortresses, unintentionally preserving the "old world" at a time when a new generation could guide society towards a better humanity"--